2018
DOI: 10.3389/fgene.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

SNP Data Quality Control in a National Beef and Dairy Cattle System and Highly Accurate SNP Based Parentage Verification and Identification

Abstract: A major use of genetic data is parentage verification and identification as inaccurate pedigrees negatively affect genetic gain. Since 2012 the international standard for single nucleotide polymorphism (SNP) verification in Bos taurus cattle has been the ISAG SNP panels. While these ISAG panels provide an increased level of parentage accuracy over microsatellite markers (MS), they can validate the wrong parent at ≤1% misconcordance rate levels, indicating that more SNP are needed if a more accurate pedigree is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…The conflict rate for sires of cows in the Mexican population was similar to the 7 to 12% reported recently for other populations. An incorrect sire was detected for 7% of the German Angeln dairy cattle population (Sanders et al, 2006), and a rate of 7 to 9% was reported for pedigree errors nationally in Ireland (McClure et al, 2018). For Holstein cows sired by AI bulls, the error rate was 11% in the United States (Banos et al, 2001) and 12% in Israel (Weller et al, 2004).…”
Section: Parentage Validationmentioning
confidence: 97%
“…The conflict rate for sires of cows in the Mexican population was similar to the 7 to 12% reported recently for other populations. An incorrect sire was detected for 7% of the German Angeln dairy cattle population (Sanders et al, 2006), and a rate of 7 to 9% was reported for pedigree errors nationally in Ireland (McClure et al, 2018). For Holstein cows sired by AI bulls, the error rate was 11% in the United States (Banos et al, 2001) and 12% in Israel (Weller et al, 2004).…”
Section: Parentage Validationmentioning
confidence: 97%
“…This pattern is especially evident among breeders of domestic cattle and sheep (Table ). Not coincidentally, the cattle breeding field has arrived at a preliminary consensus that 500 or more SNPs are required to resolve parentage confidently (e.g., McClure et al, ; McClure et al, ), whereas fields using modern analytical methods tend to conclude that 100–200 SNPs are usually more than adequate (Abadía‐Cardoso, Anderson, Pearse, & Garza, ; Dussault & Boulding, ; Steele et al, ). The reason that exclusion performs less well than formal maximum‐likelihood approaches is that it requires implicit assumptions that are ill defined and it discards much of the data.…”
Section: Approaches To Parentage Analysismentioning
confidence: 99%
“…Since the availability of both the ISAG 100 and ISAG 200 panels for bovine parentage validation, more recent studies have highlighted the potential limitations of using a relatively small number of SNP (Strucken et al, 2016 ; McClure et al, 2018 ). Due to large-scale genotyping in most world countries the trend is toward large numbers of SNP in combination with different levels of quality control to ensure a high accuracy (McClure et al, 2018 ). The application of SNP based parentage is only cost-effective if it forms part of routine genotyping.…”
Section: Application Of Genomics In South Africamentioning
confidence: 99%